2017
DOI: 10.7150/jca.19964
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Combined Transcatheter Arterial Chemoembolization and CT-guided Radiofrequency Ablation with Surgical Resection in Patients with Hepatocellular Carcinoma within the Up-to-seven Criteria: A Multicenter Case-matched Study

Abstract: Background & Aims: We compared the efficacy of transcatheter arterial chemoembolization (TACE) in combination with CT-guided radiofrequency ablation (RFA) with that of surgical resection (SR) in patients with hepatocellular carcinoma (HCC) within the up-to-seven criteria.Methods: From January 2004 to December 2014, 420 multicenter consecutive patients with HCC who conformed to the up-to-seven criteria and initially received either TACE plus CT-guided RFA (TACE-RFA) or SR were enrolled. A matched cohort compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 29 publications
1
29
1
Order By: Relevance
“…It indicated that DEB-TACE combined with RFA can achieve the same short-term effects as surgical treatment. In terms of liver damage, the results implied that the treatment of DEA-TACE combined with RFA had less damage to the liver than surgical treatment, which is similar to the results of the Pan et al[ 45 ]. In terms of complications, it indicated that patients treated with DEB-TACE combined with RFA showed better tolerance.…”
Section: Discussionsupporting
confidence: 84%
“…It indicated that DEB-TACE combined with RFA can achieve the same short-term effects as surgical treatment. In terms of liver damage, the results implied that the treatment of DEA-TACE combined with RFA had less damage to the liver than surgical treatment, which is similar to the results of the Pan et al[ 45 ]. In terms of complications, it indicated that patients treated with DEB-TACE combined with RFA showed better tolerance.…”
Section: Discussionsupporting
confidence: 84%
“…The OS in the TR group was significantly prolonged compared to that in the HT group. Pan et al 10 compared surgical resection with the combination of TACE with RFA for HCC. The median OS and the 1-, 3-, and 5-year survival rates were 61.0 months and 94.4%, 83.6%, and 49.5%, respectively, in the resection group and 55.0 months and 95.6%, 80.8%, and 40.6%, respectively, in the combination group.…”
Section: Discussionmentioning
confidence: 99%
“… 9 There are only few reports, with a small number of patients, which focus on the comparison between TACE with RFA and hepatectomy for HCC beyond the Milan criteria. 10 12 So, we retrospectively analyzed clinical data of TACE combined with RFA and hepatectomy in newly diagnosed HCC patients, comparing the efficacies of the two treatment methods and analyzing the prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is still one of the most common tumors in the world and the second most common cause of cancer death [1,2]. Although ultrasound and serum alpha-fetoprotein (AFP) levels monitor high-risk populations for early detection of HCC, most patients are diagnosed as advanced stages [3][4][5]. Moreover, some cirrhosis patients with insufficient liver reserves may not be suitable for hepatectomy [6,7].…”
Section: Introductionmentioning
confidence: 99%